Practices of Filipino Public High School Teachers on Digital Teaching and Learning Technologies during the COVID-19 Pandemic - Javier, Babylyn F. (International Journal of Computing Sciences Research, 2022)
Purpose – With industry 4.0 revolutionizing the digitally renowned teaching and learning societies, this research study aims to uncover the practices of public high school teachers on digital teaching and learning technologies during the COVID-19 pandemic.  Method – This descriptive-correlational study surveyed 34 consented Filipino teacher-participants of a public high school system in the Buguey District, Northern Philippines. Validated responses extracted thru Google forms administered in 30 days were described using frequency counts and percentages. Perceived practices were correlated with teacher-participants' profiles, while qualitative key informant interviews disclosed best practices, challenges, and problems along with the use of digital technologies for teaching and learning. Results – Findings revealed rare practices on the use of digital technologies to teaching and learning during the COVID-19 pandemic among teachers which are mostly on early to middle age brackets, dominantly female, completed their equivalent Masters' degree, holding teacher 2 or 3 ranks, and permanently teaching in 6 to 10 years now. Practices of teachers in the use of digital teaching and learning tools are somewhat evident, eager to practice and acknowledging the benefits of using the digital tools and radiating best practices in the workplace. Despite some technical issues that are beyond control, having internet at home necessitates the teacher's role to enhance teaching and learning while maximizing the potential of varied tools. Conclusion – With the onslaught of the COVID-19 pandemic, the Department of Education (DepEd) has indeed necessitated teachers to be innovative in class towards achieving its vision-mission statement by integrating into the curriculum and instruction the use of digital teaching and learning tools. Recommendations – It is recommended that DepEd must continually upscale its technological competencies with the implementation of the proposed learning action cell sessions.   Research Implications – The relevant research findings provided insights for school administrators for implementing training sessions for teachers to be technologically pandemic-responsive. Practical Implications – The results of the study provided inputs for teachers to be adaptive to utilizing digital tools for teaching not only in time of a pandemic.